Humoral immune response of mice against a vaccine candidate composed of a chimera of gB of bovine alphaherpesviruses 1 and 5 - Quintero Barbosa, Juan Sebastián (2023)
Infectious bovine rhinotracheitis (IBR) and bovine meningoencephalitis are caused by Bovine alphaherpesvirus (BoHV) types 1 and 5, which seriously threaten the global cattle industry. Vaccination to improve immunity is the most direct and effective means to prevent these conditions. Glycoprotein B (gB) is essential for the attachment of both viruses to permissive cells, and is a major target of the host immune system, inducing a strong humoral response. The aim of this study was to evaluate, in a murine model, the immune response of a candidate vaccine formulation composed of a chimeric BoHV-1 and BoHV-5 gB (DgB), expressed in Komagataella phaffii. The chimeric DgB vaccine adjuvanted with Montanide 50 ISA V2 or aluminum hydroxide was administered intramuscularly or subcutaneously. A control group and a group that received a commercial vaccine were inoculated subcutaneously. Higher titers of neutralizing antibodies against BoHV-1, BoHV-5, and a natural BoHV-1/5 recombinant strain were obtained with the oil-based candidate vaccine formulation administered intramuscularly. The results demonstrated that the chimeric DgB conserved important epitopes that were able to stimulate a humoral immune response capable of neutralizing BoHV-1, BoHV-5, and the recombinant strain, suggesting that the vaccine antigen is a promising candidate to be further evaluated in cattle.